Rancang Bangun Robot Beroda dengan Kemampuan Berjalan Pada Sudut Tanjakan Landai dan Transmisi Sinyal Kendali Berbasis Bluetooth - Akhmad Rizal Dzikrillah; Muhammad Rafli Ardiansyah; Rizky Afif Afandi; Elvira Nur Rahma; Muhammad Fajar Nugroho; Muhammad Shafar Rahim; Ahmad Robi (Prosiding Seminar Nasional Teknoka, 2023)
In the 2023 ABU-Robocon (KRAI) robot contest, robots were instructed to insert rings into the poles of an arena in the form of a stacked floor. To maximize the score, the robot is allowed to climb the level 2 temple floor. Connecting the level 2 temple floor and the base of the arena is a ramp board with an incline angle of 18,420 and an area of 600 x 975 mm2. Another rule is that athletes controlling manual robots are not allowed to enter the arena or must stay outside the arena. This research aims to design a wheeled robot that has the ability to traverse uphill roads in the KRAI robot arena as well. The robot can be controlled remotely so that athletes do not need to enter the arena which has an area of 12x6 m2. The use of 4 omniwheels which are given a total DC voltage of 14.8 V, is able to make the aluminum robot able to traverse uphill roads in the KRAI 2023 robot arena. By using Bluetooth transmission, the robot can be controlled wirelessly across the entire arena.